MENCARI TELUR GARUDA Video Fitur Multi Kanal - Nanang R. Hidayat (SURYA SENI, 2009)
Looking for the Egg of Garuda: Multi Channel Video Feature. Republic of Indonesia proclaimed its independence on 17th August 1945. As an inde-pendent nation, the people of Indonesia considered the “Garuda Pancasila” – asymbolic eagle like bird standing for the state ideology named Pancasila - as theofﬁ cial symbol of  the country.Ironically the history of that country symbol has never been noticed in thestate history. This is the question: why has such an important history never beendocumented by Indonesian historians? Whereas, the greatness of nations couldbe measured by how they could appreciate their history. Whilst, now more andmore, the meaning of Pancasila as the state principle is fading away, or manypeople begin forgetting its signiﬁ cance.‘Looking for the egg of Garuda’ is an expression to metaphorise an effortto ﬁ nd out where did our country symbol come from. Who were the people involvedin the designing process of Garuda as the state symbol.This video being displayed in a documentary feature format,  tries to relivethat very moment  in shape of “Wayang Suluk”, showed in multi-canal way asa new alternative to learn the history, in hope that this presentation can increasethe pride of , as well as affection to our motherland.Keywords: Garuda Pancasila, Important Historical, and Wayang Suluk